Dialogue among civilizations: A historical perspective - Mohamad Zaidin, Mat@Mohamad; Sofyuddin, Yusof; Ahmad Zahid, Salleh; Abdillah Hisham, Ab. Wahab (2017)
This article discusses the developmental history of “dialogue among civilizations”, which begins with the emergence of the term until the modern era. This article found that fluctuations in the debate on “dialogue among civilizations” were influenced by current global situations, especially that of global politics. The French-Muslim philosopher Roger Garaudy (aka Ragaa Garaudy) first coined the term “dialogue among civilizations” around the 70s and it then attracted the attention of societies around the world, both in the West and in the East.